The genetic basis of cooperative aggregation in the green alga Chlamydomonas reinhardtii - Berger, Christopher Michael (Kansas State University, 2017)
Unicellular organisms alter their behavior and morphology in response to environmental stresses, particularly in response to immediate threats to their survival. A common tactic of predator avoidance for unicellular green algae is to aggregate to form groups. We have found that the model unicellular green algae Chlamydomonas reinhardtii forms aggregates in response to the presence of the filter feeding zooplanktonic predator, Daphnia magna. Chalmydomonas is a member of the volvocine algae, a morphologically diverse group of closely related green algae that is often used to study multicellular development. We have characterized aggregation in Chlamydomonas reinhardtii and found that it is rapid, transient and induced by signals originating from the Daphnia predators. To understand the genetic basis of cooperative aggregation we used an RNA-seq approach. RNA-seq characterized the transcriptomic response by Chlamydomonas during aggregation, and we identified 131 genes are significantly differentially expressed between predated and unpredated cultures of Chlamydomonas. Several candidate genes were characterized based on existing annotations, evolutionary history and expression profile. Evolutionary relationships between candidate aggregation genes in Chlamydomonas and their orthologs in multicellular Volvocales suggest a possible role of aggregation genes in multicellular development. Our results demonstrate that Chlamydomonas dynamically alters its morphology based on its environment and identify several candidate genes for aggregation and multicellular development.
Keywords: Chlamydomonas reinhardtii; Daphnia; Cooperative aggregation; Multicellular evolution; Volvocales; Predation